Scientific views of world linguists on terms of craft - Abduvalieva Xulkaroy Lutfulla qizi (Zien Journals, 2024)
This article presents an overview of the scientific perspectives among world linguists on the terms of craft. It explores how linguists understand and analyze the terminology used in craft. Through empirical studies and theoretical frameworks, linguists examine the evolution, cultural aspects, and specialized usage of terms in this domain. Furthermore, this article delves into the impact of terminology on communication, cognitive processing, and translation. By shedding light on the linguistic examination of terms of craft, this article contributes to understanding how language shapes and influences various professional disciplines.
Keywords: terms; terminology; cognitive